Strength of farmers' knowledge and participation in crop improvement and managing agrobiodiversity on-farm - Chaudhary, P.; Khatiwada, S.P.; Joshi, Krishna D. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
This paper highlights the role of fanners in crop improvement and managing agro biodiversity. The fiddling’s are mostly based on focus-group discussions and field observations. Documentation of farmers' knowledge and experiences in crop improvement and managing agro biodiversity may serve as a reference for individual breeders or institutions involved in participatory crop improvement through differed strategies like participatory plant breeding, participatory varietal selection, of participatory germplasm enhancement. The strength of participatory crop improvement is that there is multistage involvement of farmers, from parent selection through to cultivation and selection of planting materials, because farmers have a wide range of knowledge and experience, and they are the end-users as well. Sine ancient times, farmers have been dependent upon the traditional seed-supply system, which still accounts for over 90% of the seed requirement in Nepal. A variety of mechanisms like varietal selection, seed selection, seed processing and storage, and the seed-flow system have contributed lo crop development, creating agro biodiversity on-farm. More recently, participatory germplasm enhancement has arisen as a new strategy to enhance the germplasm of local landraces, which will not only empower farmers in improving their landraces but also strengthen in situ conservation of such landraces on-farm. The current need is to incorporate farmers' relevant knowledge and use it in the overall crop-improvement process.